Comparative Transcriptome Analysis of Flower Senescence of Camellia lutchuensis - Liu, Weixin; Yin, Hengfu; Feng, Yi; Yu, Suhang; Fan, Zhengqi; Li, Xinlei; Li, Jiyuan (Current Genomics, 2022)
Background: Flower senescence is the last stage of flower development and affects the ornamental and economic value of flower plants. There is still less known on flower senescence of the ornamental plant Camellia lutchuensis, a precious species of Camellia with significant commercial application value. Methods: Transcriptome sequencing was used to investigate the flower senescence in five developmental stages of C. lutchuensis. Results: By Illumina HiSeq sequencing, we generated approximately 101.16 Gb clean data and 46649 differentially expressed unigenes. Based on the different expression pattern, differentially expressed unigenes were classified into 10 Sub Class. And Sub Class 9 including 8252 unigenes, was highly expressed in the flower senescent stage, suggesting it had a potential regulatory relationship of flower senescence. First, we found that ethylene biosynthesis genes ACSs, ACOs, receptor ETR genes and signaling genes EINs, ERFs all upregulated during flower senescence, suggesting ethylene might play a key role in the flower senescence of C. lutchuensis. Furthermore, reactive oxygen species (ROS) production related genes peroxidase (POD), lipase (LIP), polyphenoloxidase (PPO), and ROS scavenging related genes glutathione S-transferase (GST), glutathione reductase (GR) and superoxide dismutase (SOD) were induced in senescent stage, suggesting ROS might be involved in the flower senescence. Besides, the expression of monoterpenoid and isoflavonoid biosynthesis genes, transcription factors (WRKY, NAC, MYB and C2H2), senescence-associated gene SAG20 also were increased during flower senescence. Conclusion: In C. lutchuensis, ethylene pathway might be the key to regulate flower senescence, and ROS signal might play a role in the flower senescence.
Keywords: differentially expressed genes